The Role of Adaptive Gamification on Students' Intrinsic Motivation: A Control Experiment in Advanced Mathematics Learning - Amelia Amelia (Return : Study of Management, Economic and Bussines, 2025)
The low intrinsic motivation of students in advanced mathematics learning is a major challenge in the world of education. This study aims to explore the influence of adaptive gamification on intrinsic motivation and student learning outcomes through a quasi-experimental approach with a pretest-posttest control group design. The sample consisted of two classes XI MIPA at one of the public high schools, where one class used adaptive gamification and the other class used conventional methods. Data were collected through motivational questionnaires, observations, and interviews, then analyzed descriptively and thematically. The results showed that the experimental group experienced significant improvements in post-test scores and intrinsic motivation compared to the control group. These findings indicate that adaptive gamification-based learning can build more personalized and meaningful learning experiences. The practical implication of this study is the need to integrate adaptive gamification technology in the learning system to support students' long-term learning motivation.